Effect of soil-moisture stress on water relation by plant and cropping behaviour in guava (Psidium guajava) - SINGH, GORAKH; RAJAN, S; PANDEY, D; SINGH, A K (The Indian Journal of Agricultural Sciences, 2013)
Effect of soil-moisture stress on relative water content, proline accumulation in leaf, fruiting behaviour and fruit quality was studied in 'Allahabad Safeda' and 'Sardar' guava (Psidium guajava L.), Stress was exerted on trees by withholding water from January to June, and the non-stressed control trees were watered at an interval of 10-15 days, depending on the evaporation. TIle abscission of flowers was noticed when relative water content reached 60.20% in 'Allahabad Safeda' and 53.40% in 'Sardar' guava. A trend was also noticed in the quantity of leaf proline according to the degree of water stress. The metabolic activity in the plants was maintained better even at low RWC in 'Sardar' than 'Allahabad Safeda'. 'Sardar' appeared more tolerant than 'Allahabad Safeda'. Water-dedficient trees had significantly lower yield during rainy season in both the varieties. However, 'Allahabad Safeda' responded more to soil moisture stress for regulation of flower to harvest and better fruit yield during winter season than 'Sardar'. In 'Sardar' in additioÂ  to soilmoisutre stress a chemical that can inhibit the growth may also be essential to regulate cropping.